Pengaruh Kebijakan Larangan Plastik dan Iklan Ramah Lingkungan Terhadap Perubahan Perilaku Konsumen di Kota Mataram - Ni Ketut Manik Wirdisari; Didy Ika Supryadi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This research is motivated by the increasing global concern about environmental pollution issue due to the use of single-use plastics. Mataram City, which has implemented a plastic ban policy, is the object of study. The main objective of this research is to analyze the extent to which the plastic ban policy and environmental-friendly advertising influence consumer behavior change in Mataram City. This study uses a quantitative approach with a survey method of 100 respondents selected purposively. The main instrument is a questionnaire, and the data is analyzed using multiple linier regression. The results show that the plastic ban policy has a significant influence on consumer behavior change, marked by an increase in the use of environmentally friendly shopping bags and awareness of environmental issues. Environmental-friendly advertising also contributes to shaping more positive consumer perceptions and attitudes towards sustainable behavior. This research provides an important contribution to the government and businesses in designing more effective communication strategies and public policies.